Inhibitory Evaluation of Sulfonamide Chalcones on β-Secretase and Acylcholinesterase - Dae Wook Kim; Heung Joo Yuk; Hye Jin Kim; Jin Hyo Kim; Hyung Won Ryu; Marcus J. Curtis-Long; Jung Keun Cho; Jae Eun Kang; Ki Hun Park (Molecules, 2012)
The action of β-secretase (BACE1) is strongly correlated with the onset of Alzheimer’s disease (AD). Aminochalcone derivatives were examined for their ability to inhibit BACE1. Parent aminochalcones showed two digit micromolar IC50s against BACE1. Potency was enhanced 10-fold or more by introducing benzenesulfonyl derivatives to the amino group: 1 (IC50 = 48.2 μM) versus 4a (IC50 = 1.44 μM) and 2 (IC50 = 17.7 μM) versus 5a (IC50 = 0.21 μM). The activity was significantly influenced by position and number of hydroxyl groups on the chalcone B-ring: 3,4-dihydroxy 5a (IC50 = 0.21 μM) > 4-hydroxy 4a (IC50 = 1.44 μM) > 2,4-dihydroxy 6 (IC50 = 3.60 μM) > 2,5-dihydroxy 7 (IC50 = 16.87 μM) > des hydroxy 4b (IC50 = 168.7 μM). Lineweaver-Burk and Dixon plots and their secondary replots indicate that compound 5a was a mixed inhibitor with reversible and time-dependent behavior. Potent BACE1 inhibitors 4a,c,f, 5a–c showed moderate inhibition against two other enzymes implicated in AD pathogenesis, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), with IC50s ranging between 56.1 ~ 95.8 μM and 19.5 ~ 79.0 μM, respectively.